Energy Metabolism and Lipidome Are Highly Regulated during Osteogenic Differentiation of Dental Follicle Cells - Oliver Pieles; Marcus Höring; Sadiyeh Adel; Torsten E. Reichert; Gerhard Liebisch; Christian Morsczeck (Stem Cells International)
Dental follicle cells (DFCs) are stem/progenitor cells of the periodontium and give rise to alveolar osteoblasts. However, understanding of the molecular mechanisms of osteogenic differentiation, which is required for cell-based therapies, is delimited. This study is aimed at analyzing the energy metabolism during the osteogenic differentiation of DFCs. Human DFCs were cultured, and osteogenic differentiation was induced by either dexamethasone or bone morphogenetic protein 2 (BMP2). Previous microarray data were reanalyzed to examine pathways that are regulated after osteogenic induction. Expression and activity of metabolic markers were evaluated by western blot analysis and specific assays, relative amount of mitochondrial DNA was measured by real-time quantitative polymerase chain reaction, the oxidative state of cells was determined by a glutathione assay, and the lipidome of cells was analyzed via mass spectrometry (MS). Moreover, osteogenic markers were analyzed after the inhibition of fatty acid synthesis by 5-(tetradecyloxy)-2-furoic acid or C75. Pathway enrichment analysis of microarray data revealed that carbon metabolism was amongst the top regulated pathways after osteogenic induction in DFCs. Further analysis showed that enzymes involved in glycolysis, citric acid cycle, mitochondrial activity, and lipid metabolism are differentially expressed during differentiation, with most markers upregulated and more markedly after induction with dexamethasone compared to BMP2. Moreover, the cellular state was more oxidized, and mitochondrial DNA was distinctly upregulated during the second half of differentiation. Besides, MS of the lipidome revealed higher lipid concentrations after osteogenic induction, with a preference for species with lower numbers of C-atoms and double bonds, which indicates a de novo synthesis of lipids. Concordantly, inhibition of fatty acid synthesis impeded the osteogenic differentiation of DFCs. This study demonstrates that energy metabolism is highly regulated during osteogenic differentiation of DFCs including changes in the lipidome suggesting enhanced de novo synthesis of lipids, which are required for the differentiation process.